Urgensi UU No 32 Tahun 2004 Tentang Pemerintahan Daerah dalam Rangka Mewujudkan Otonomi Desa: (Studi Kasus di Desa Tanjung Kecamatan Koto Kampar Hulu Kabupaten Kampar) - Candra Asmara; Ermansyah (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
Principal focus this Research is study deeper about execution of countryside governance [in]Countryside of Foreland of District of Koto of Kampar of Pate; Upstream of Kampar Sub-Province inorder to realizing countryside autonomy, but practically countryside governance not yet can be realized effectively and efficient. Its form [is] countryside governance not yet seen from ability from Countryside of Foreland of District of Koto of Kampar of Pate; Upstream of Kampar Sub-Province, in managing finance of countryside and countryside institute, what not yet measure up to the independence in the countryside governance execution. Implementation from Number Law 32 Year 2004 in realizing countryside governance in Countryside of Countryside of Foreland of District of Koto of Pate; Upstream Kampar, goods have of course get various resistance. As for resistance which researcher find in executing countryside governance[in] Countryside of Countryside of Foreland of District of Koto of Pate; Upstream Kampar is not yet made available of good human resource ability and professional, finance which not yet adequate, availibility of equipments and facility which still minim and execution of governance management which uncommitt better. This matter cause its form not yet otoomi countryside, specially [in] Countryside of Countryside of Foreland of District of Koto of Pate; Upstream Kampar.